The critical role of point defects in improving the specific capacitance of δ-MnO2 nanosheets - Peng Gao (Nature Portfolio, 2017)
Two-dimensional solids are of interest for energy storage due to their large accessible surface area, enabling rapid charge/discharge. Here, the authors quantify the point defects in oxide nanosheets, demonstrating that intentional introduction of charged point defects improves the charge storage behaviour.